Rotilicious Bakery Sdn Bhd / Mazliani Mohd Muslim, Norshuhada Shaari … [et al.] - MOHD MUSLIM, MAZLIANI; SHAARI, NORSHUHADA; GALA, NURUL FAZILA; NOORZAMBRE, NURUL SHUHADA; ABD HADI, FATIN SYAFIKAH (2019)
Rotilicious Bakery is a business that will run makers, receive orders and distributor of bakery based product such as bread such as croissant, focaccia, crumpet and various types of breads. Not only that, we also provide a variety of cake. Business is strategically located in the area of Bandar Baru Bangi. Rotilicious Bakery will first and foremost provide delicious baked goods, with an emphasis on healthful indulgence. By providing organic, gluten-free and vegan baked goods. Not only that, when looking at our country's economy today it is not easy to run the business. The idea of opening the Rotilicious Bakery is to increase our team incomes impartially in the future. It all comes from the hobby of one of us who loves to make a bread and cake in the spare time so she has put her idea to build Rotilicious Bakery and businessmen involved in starting our business plan are Nurul Fazila Binti Gala, Mazliani Binti Muslim, NorShuhada Binti Shaari, Fatin Syafikah Binti Abd Hadi and Nurul Shuhada Binti Noorzambre